Islamic Pacifism: An Ethico-Theological Examination of Peace and Nonviolence in Islam - Abdulaev, Sabina (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
Islam calls for the avoidance of violence, if possible, or at least its minimization and use only as the last resort. The purpose of this study is to highlight the roots of pacifism in Islam; the primary sources studied are the main Muslim theological texts—the Qur’an and Sunnah (the Prophetic tradition). After analyzing these two sources, I claim that Islam and ‘devout pacifism’ are compatible. Islam calls Muslims to be faithful, decent, and good human beings, who respect the life and property of others, Muslim and non-Muslim. A model of the devout Muslim pacifist is not different from the universal model, but similar to that found in other civilizations and cultures. According to both sources, Islamic pacifism derives from human obedience to Allah, just as in other monotheistic religions that promote peaceful solutions to internal and external crises, domestic and foreign. This paper offers a new perspective on nonviolence in Islam, ethico-theological justification of war, and applications of jihad and violence as factors in managing political relations among Muslims and between Muslims and non-Muslims.